RF circuit design techniques for MF-UHF applications - Eroglu, Abdullah (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2013)
'An excellent resource for professionals and students, this book presents practical, unique design techniques and application examples that can be used to design RF components and systems at the MF-UHF range. It covers a variety of topics including pulsing switch-mode amplifier design, high power microstrip circuit design, novel power measurement devices, and composite and multi-layer inductor design. The text provides detailed design process for engineering application examples, illustrating how to implement theory into practice. The book also includes unique Matlab and Mathcad codes'--
Includes bibliographical references and index.
Keywords: Radio circuits